2020
DOI: 10.5194/amt-13-1563-2020
|View full text |Cite
|
Sign up to set email alerts
|

Distributed observations of wind direction using microstructures attached to actively heated fiber-optic cables

Abstract: Abstract. The weak-wind boundary layer is characterized by turbulent and submesoscale motions that break the assumptions necessary for using traditional eddy covariance observations such as horizontal homogeneity and stationarity, motivating the need for an observational system that allows spatially resolving measurements of atmospheric flows near the surface. Fiber-optic distributed sensing (FODS) potentially opens the door to observing a wide range of atmospheric processes on a spatially distributed basis an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…L ↓ and L ↑ (W m −2 ) are the average downward and upward longwave radiation fluxes, respectively, and is the FO cable surface emissivity. Based on the kind of stainless steel, emissivity values can range from 0.3 to 0.7 (Baldwin and Lovell-Smith, 1992); however, we assume a value of 0.5 (Madhusudana, 2000). σ is the Stefan-Boltzmann constant, 5.67 × 10 −8 (W m −2 K −4 ), and σ T 4 s is the outgoing longwave radiation of the fiber, i.e., L fiber ; h is the convective heat transfer coefficient (W m −2 K −1 ).…”
Section: Dts and Signal-to-noise Ratio Analysismentioning
confidence: 99%
“…L ↓ and L ↑ (W m −2 ) are the average downward and upward longwave radiation fluxes, respectively, and is the FO cable surface emissivity. Based on the kind of stainless steel, emissivity values can range from 0.3 to 0.7 (Baldwin and Lovell-Smith, 1992); however, we assume a value of 0.5 (Madhusudana, 2000). σ is the Stefan-Boltzmann constant, 5.67 × 10 −8 (W m −2 K −4 ), and σ T 4 s is the outgoing longwave radiation of the fiber, i.e., L fiber ; h is the convective heat transfer coefficient (W m −2 K −1 ).…”
Section: Dts and Signal-to-noise Ratio Analysismentioning
confidence: 99%
“…Indeed, the difference of temperature measured between an electrically heated and a non-heated FO cable is directly dependent on water fluxes (Bense et al, 2016;Read et al, 2014;Sayde et al, 2015), offering the possibility to determine fluxes and their spatial distribution over a large range with an excellent accuracy (Simon et al, 2021). Active heat tracer experiments using fiber-optic DTS have been used to estimate wind speed in the low atmosphere (Lapo et al, 2020;Sayde et al, 2015), in dam monitoring (Ghafoori et al, 2020;Perzlmaier et al, 2004;Su et al, 2017), for groundwater fluxes measurements in open (Banks et al, 2014;Klepikova et al, 2018;Read et al, 2014Read et al, , 2015 and sealed boreholes (Munn et al, 2020;Selker and Selker, 2018) or else in direct contact within sedimentary aquifers (del Val et al, 2021;des Tombe et al, 2019). Despite promising developments, active-DTS methods have been seldom used in hydrology to estimate groundwater/surface water interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The cable jacket adds surface and volume, making the measurement more susceptible to the local energy balance terms (Thomas et al, 2012;de Jong et al, 2015). Hence, micro-meteorological studies with DTS have primarily been demonstrated for conditions of nocturnal darkness (Keller et al, 2011;Thomas et al, 2012;Zeeman et al, 2015) or, after adjustments, taking advantage of a differentiating thermal signal governed by wind, evaporation or shading of sunlight (Petrides et al, 2011;Euser et al, 2014;Sayde et al, 2015;Lapo et al, 2020;Schilperoort et al, 2018;van Ramshorst et al, 2020). Fibre-optic cable can be deployed to form a mesh of horizontal and vertical profiles in complex geometries from the ground up.…”
Section: Introductionmentioning
confidence: 99%